THE EXPERIENCES OF CURRENTLY AND FORMERLY INCARCERATED WOMEN IN A TIME OF PANDEMIC: IMPLICATIONS FOR LIFE-GIVING COMMUNITIES - D.T.M. Veloso (Acta Theologica)
This article assesses the adequacy of the church’s responses to women currently and formerly in conflict with the law in the Philippines and offers feminist theological reflections on the need for gender- and culturally sensitive pastoral services for them in a time of pandemic. Drawing upon case studies and interviews, this paper examines the lived experiences and social worlds of women who currently occupy or formerly held the status of persons deprived of liberty. The researcher discusses the common themes and nuances in the issues and challenges they confront from behind bars and in free society, and their struggles for survival throughout the pandemic. This paper also examines their service needs and, in the case of those released from the penitentiary, the salient factors that contribute to the risk of recidivism. The researcher discusses the implications of the issues and service needs of justiceinvolved women for building life-giving communities.